The new rigid element for laminated cylindrical shell - Lovón, Oscar Bayardo Ramos (2014)
Thermal effects are incorporated into developed discrete layer mechanics for two-dimensional cylindrical shells structures. Finite element equations are developed according to layerwise theory of laminated structure. Following the layerwise theory, a variable kinematic model that incorporates mechanics and thermal conditions is also presented. The new element has a field of displacement compatible with the cylindrical shell element or plate and it can be used as a rigid element for this structural element.In the laminate model construction, adjacent layers are arranged as bonded layers. The layer has a unique constant thickness that can be different to each layer. The fiber reinforced is used and the fibers in a laminate may be oriented arbitrarily. The shear stress is adopted equal to zero because the thin thickness, on the other hand, the normal stress is maintained in order to ensure the compatibility of stress in material. The previously authors of this methods neglect the implications of thermal effects on cylindrical shells structures. Thermal effects become important when the structure has to operate in either extremely hot or cold temperature environments. These extreme conditions may severely affect the response of structure in two distinct ways: (1) induction of thermal stresses due to differences in the coefficients of thermal expansion between the various composite plies and layers and (2) temperature dependence of the elastic properties. Only a limited amount of work has been reported concerning this topic. All in all, the main contribution of this work is the consideration of this kinematic for cylindrical shells that incorporate mechanics and thermal conditions. In addition, numerical results are presented to demonstrate the capability of the current formulation to represent the behavior of cylindrical shells with these characteristics